NEW VARIABLE STAR IN THE ORION CONSTELLATION - Brjukhanov, I. S.; Goranskij, V. P. (Одеські астрономічні публікації, 2017)
New variable star with α = 05° 57m22s, δ = +20°15.5' (1950) was discovered with elements JD Max=2436999.28 + 0.2343973 E, range 15.6- 16.2m (pg) and asymmetry M-m=0.26.